Room-temperature Operation of Lithium Sulfide Positive and Silicon Negative Composite Electrodes Employing Oxide Solid Electrolytes for All-solid-state Battery - Hiroshi NAGATA; Junji AKIMOTO (Electrochemistry, 2022)
Oxide-type all-solid-state batteries are expected to be the next-generation batteries owing to their safety performance. Similarly, Li2S and Si are also attracting attention as next-generation active materials owing to their high theoretical energy density. However, battery performances and manufacturing methods are associated with many challenges. Thus, this study focuses on an effective method for manufacturing Li2S positive and Si negative composite electrodes for oxide-type all-solid-state Li2S–Si batteries. These composite electrodes are prepared via a one-step mechanical milling process using Li2S or Si as the active materials, carbon with a high specific surface area, and raw materials of oxide glass electrolyte. A solid electrolyte (SE), as well as composites of the active materials, SE, and carbon, are simultaneously generated via this process. Thereafter, the all-solid-state Li2S–Si full battery cell comprising Li2S positive and Si negative composite electrodes, respectively, as prepared via the cold press technology, exhibits a relatively high energy density of 283 Wh kg−1 (sum of the masses of the positive and negative composite electrodes) and an area capacity of 4.0 mAh cm−2 at 0.064 mA cm−2 and 25 °C.